Keloid treatments: an evidence-based systematic review of recent advances - Laura A. Walsh; Ellen Wu; David Pontes; Kevin R. Kwan; Sneha Poondru; Corinne H. Miller; Roopal V. Kundu (Systematic Reviews, 2023)
Abstract Background Keloids are pathologic scars that pose a significant functional and cosmetic burden. They are challenging to treat, despite the multitude of treatment modalities currently available. Objective The aim of this study was to conduct an evidence-based review of all prospective data regarding keloid treatments published between 2010 and 2020. Methods A systematic literature search of PubMed (National Library of Medicine), Embase (Elsevier), and Cochrane Library (Wiley) was performed in November of 2020. Search strategies with the keywords “keloid” and “treatment” were performed by a medical librarian. The search was limited to prospective studies that were peer-reviewed, reported on clinical outcomes of keloid therapies, and were published in the English language between January 1, 2010, and November 24, 2020. Results A total of 3462 unique citations were identified, of which 108 studies met inclusion criteria. Current literature supports silicone gel or sheeting with corticosteroid injections as first-line therapy for keloids. Adjuvant intralesional 5-fluorouracil (5-FU), bleomycin, or verapamil can be considered, although mixed results have been reported with each. Laser therapy can be used in combination with intralesional corticosteroids or topical steroids with occlusion to improve drug penetration. Excision of keloids with immediate post-excision radiation therapy is an effective option for recalcitrant lesions. Finally, silicone sheeting and pressure therapy have evidence for reducing keloid recurrence. Conclusions This review was limited by heterogeneity of subject characteristics and study outcome measures, small sample sizes, and inconsistent study designs. Larger and more robust controlled studies are necessary to further understand the variety of existing and emerging keloid treatments, including corticosteroids, cryotherapy, intralesional injections, lasers, photodynamic therapy, excision and radiation, pressure dressings, and others.